Old and New Minorities: Diversity Governance and Social Cohesion from the Perspective of Minority Rights - Medda-Windischer Roberta (Acta Universitatis Sapientiae: European and Regional Studies, 2017)
Minority rights instruments have been traditionally applied to old minority groups. This paper examines to what extent these same instruments are conceptually meaningful to the integration of new minorities stemming from migration. The conviction that minority groups, irrespective of their being old or new minorities, have some basic common claims that can be subsumed under a common definition does not mean that all minority groups have all the same rights and legitimate claims: some have only minimum rights, while others have or should be granted more substantial rights; some can legitimately put forward certain claims – not enforceable rights – that need to be negotiated with the majority, while others should not. In order to devise a common but differentiated set of rights and obligations for old and new minority groups, it is essential to analyse the differences and similarities of both categories of minorities, their claims, needs, and priorities; in this way, it will be possible to delineate a catalogue of rights that can be demanded by and granted to different minority groups. Studying the interaction between traditional minorities and migrants or old and new minority groups is a rather new task because so far these topics have been studied in isolation from each other. It is also an important task for future research in Europe since many states have established systems for the rights of old minorities but have not as yet developed sound policies for the integration of new minority groups stemming from migration.